Correlation Between Madrasah Principal Behavior, Work Ethics and Empowerment of Madrasah Principals and Career Growth of State Aliyah Madrasah Teachers in Jambi Province - Ahmadi, Ahmadi; Mukhtar, Mukhtar; Risnita, Risnita (Greenation International Journal of Law and Social Sciences, 2024)
This article discusses and analyzes about. Correlation between Madrasah Culture, Leadership Style and Work Ethics of Madrasah Heads and Career Growth of State Madrasah Aliyah Teachers in Jambi Province. This literature review article writing method uses library research methods sourced from online media such as Google Scholar, Mendeley and/or other academic online media. The results of this article are: a). The relationship between the behavior of madrasah principals (X1) and teacher career growth (Y). B). The relationship between empowerment of madrasa heads (X2) and teacher career growth (Y). c). The relationship between the Madrasah Head's Work Ethics (X3) and teacher career growth (Y). d). The relationship between the behavior of the madrasah head (X1), the empowerment of the madrasah head (X2) and the work ethics of the madrasah head (X3) together with teacher career growth (Y).